Helsingin Sanomien kuvat Krimin valtaamisesta 2014 - Latvala, Maria (Tiede ja ase, 2017)
The actions in Crimea increased the general understanding of the possibilities for military actions at the level of mental images. is research discusses the photographs presented in the Helsingin Sanomat newspapers news regarding the occupation of the Crimea in 2014. In our information environment pictures represent the events better than text. is article explains how conscious mental images are formed of the illegal annexation of the Crimea in the pictures used in Helsingin Sanomat. e meaning of the photos is explained by using semiotics and the functional theory of language. e photos are also analyzed with their respective themes. e collection time for the material is from February 28th to March 17th 2014, with the used number of photos and their captions adding up to 42 in total. e analysis shows that the command in the Crimea Peninsula appears to have been with the Russians already on March 5th 2014. e situation does not appear like an occupation. e rearms on display are mainly held by Russian soldiers, with the exception of two people who cannot be recognized as Ukrainian representatives. In only one photo a pro- Ukrainian man is assaulted with a gun stock, which appeared in the pictures to be the strongest act of violence by the local people. If the occupation and the few armed men are disregarded in the studied photographs, the photograph representation delivers a normal, legal situation apart from the assault. e Russian soldiers are pictured acting like peacekeepers. e referendum on the status of Crimea before its illegal annexation to Russia was represented as legal. e study concludes that the pictures show the occupation resulted into more good actions than bad.